2015
DOI: 10.1088/0964-1726/24/11/115015
|View full text |Cite
|
Sign up to set email alerts
|

Semi-active damping with negative stiffness for multi-mode cable vibration mitigation: approximate collocated control solution

Abstract: This paper derives an approximate collocated control solution for the mitigation of multi-mode cable vibration by semi-active damping with negative stiffness based on the control force characteristics of clipped linear quadratic regulator (LQR). The control parameters are derived from optimal modal viscous damping and corrected in order to guarantee that both the equivalent viscous damping coefficient and the equivalent stiffness coefficient of the semi-active cable damper force are equal to their desired coun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 46 publications
1
34
0
Order By: Relevance
“…Results showed that a nonlinear damper could effectively suppress cable motion containing a wide range of modes and was, therefore, more advantageous than linear dampers in multimode vibration control. More recently, Weber and Distl introduced a semi‐active control scheme for multimode cable vibration mitigation. It is based on the approximate collocated solution of a clipped negative‐stiffness viscous damper optimized by the linear quadratic regulator (LQR) method and requires real‐time measurement of the damper stroke and force.…”
Section: Introductionmentioning
confidence: 99%
“…Results showed that a nonlinear damper could effectively suppress cable motion containing a wide range of modes and was, therefore, more advantageous than linear dampers in multimode vibration control. More recently, Weber and Distl introduced a semi‐active control scheme for multimode cable vibration mitigation. It is based on the approximate collocated solution of a clipped negative‐stiffness viscous damper optimized by the linear quadratic regulator (LQR) method and requires real‐time measurement of the damper stroke and force.…”
Section: Introductionmentioning
confidence: 99%
“…As expected, the damping coefficient almost remains a constant with the increase of the mode order of the cable for each circuit, while the negative stiffness increases with the increase of the mode order. However, the optimum negative stiffness for a stay cable does not depend on the mode number [36,37]. Hence, the DC generator with frequency-dependent negative stiffness may be better than viscous damping only, but is still suboptimal when compared with optimum viscous damping with negative stiffness for cable vibration control.…”
Section: The Stay Cable With Electromagnetic Damping Alonementioning
confidence: 99%
“…Furthermore, the forcedisplacement trajectories exhibit the negative stiffness behavior provided by the self-sensing MR damper. The negative stiffness force yields the reduced local stiffness of the cable at the damper position, which augments the amplitude of the damper displacement to dissipate increased amount of vibrational energy due to the improved cable damping [25] and, hence, results in overall better control performance. control performs better than the optimal passive MR control, when is larger than 0.01, with 17.4%, 7.4%, 12.5%, and 22.2% further reductions of RMS cable displacement compared to the optimal passive case at the damper locations of 0.02 , 0.03 , 0.04 , and 0.05 , respectively.…”
Section: Efficacy Of Different Control Schemesmentioning
confidence: 99%
“…However, the passive dampers may potentially lead to insufficient damping to other concerned modes without increasing the damper installation location that may undesirably affect the esthetics of the bridge [12,13], especially for very long cables. Alternative promising solution to cable vibration mitigation is semiactive control based on controllable magnetorheological (MR) dampers due to their real-time adjustable damping effect, fail-safe behavior, and superior energy dissipation over passive dampers [2,6,[14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation